2013
DOI: 10.1148/rg.331125011
|View full text |Cite
|
Sign up to set email alerts
|

Emergent Complications of Assisted Reproduction: Expecting the Unexpected

Abstract: With the increasing popularity of assisted reproductive technology (ART), radiologists are more likely to encounter associated complications, especially in an emergency setting. These complications include ovarian hyperstimulation syndrome (OHSS), ovarian torsion, and ectopic and heterotopic pregnancy. OHSS occurs following ovulation induction or ovarian stimulation and manifests with bilateral ovarian enlargement by multiple cysts, third-spacing of fluids, and clinical findings ranging from gastrointestinal d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 46 publications
(79 reference statements)
0
31
0
Order By: Relevance
“…Embryo and oocyte cryopreservation may be associated with ovarian hyperstimulation syndrome (OHSS), an exaggerated response to ovarian stimulation resulting in increased capillary permeability (11). Clinical signs/symptoms, imaging findings (ovarian size, presence of ascites, and pleural effusions), and biochemical parameters are combined to grade OHSS as mild, moderate, or severe (12).…”
Section: Part I: Fertility-sparing Using Assisted Reproductive Technomentioning
confidence: 99%
See 2 more Smart Citations
“…Embryo and oocyte cryopreservation may be associated with ovarian hyperstimulation syndrome (OHSS), an exaggerated response to ovarian stimulation resulting in increased capillary permeability (11). Clinical signs/symptoms, imaging findings (ovarian size, presence of ascites, and pleural effusions), and biochemical parameters are combined to grade OHSS as mild, moderate, or severe (12).…”
Section: Part I: Fertility-sparing Using Assisted Reproductive Technomentioning
confidence: 99%
“…Ovaries acquire a characteristic ‘spoke wheel’ appearance due to multiple peripheral ovarian cysts surrounding the central ovarian stroma (11, 13, 14) (Figure 1). Enlarged cystic ovaries should not be mistaken for cystic ovarian neoplasm (14).…”
Section: Part I: Fertility-sparing Using Assisted Reproductive Technomentioning
confidence: 99%
See 1 more Smart Citation
“…Several behavioral risks have been linked to EP, including smoking and STDs [1, 36]. Disruption of ciliary function related to smoking is a reported risk factor for EP [6].…”
Section: Discussionmentioning
confidence: 99%
“…Although studies have found that only 1–2 % of pregnancies in the United States are ectopic and deaths due to EP are decreasing, EP remains an important cause of morbidity and mortality and there are opportunities for prevention [2]. Risk factors for EP include: a history of assisted reproductive technology use; endometriosis; previous obstetrical or gynecological surgery, including tubal sterilization and cesarean section; tubal inflammation and scarring due to infections such as chlamydia and gonorrhea; and disruption of ciliary function attributable to smoking [1, 36]. Women affected are not only exposed to complications from the ectopic pregnancy itself and the related treatment procedures, but are also at greater risk of another ectopic pregnancy and infertility [2].…”
Section: Introductionmentioning
confidence: 99%